The Use of the Melajari Website in Cultural Arts Education and Its Impact on the Learning Outcomes of Grade 11 Students at MA Hidayatullah Martapura - Maimunah, Maimunah; Susanti Sufyadi; Agus Hadi Utama (Jurnal Evaluasi dan Pembelajaran, 2025)
Along with the independent curriculum, the educational world in Indonesia has begun a transition to digital learning. However, the use of learning media is still minimal in several schools that support it, which can hinder the understanding of learning, especially visual learning, such as artistic learning. This study seeks to determine the strategy for utilizing the Melajari website and its influence on student learning outcomes in the area of artistic and cultural dance. The research method was qualitative descriptive, with 11 grade students at MA Hidayatullah Martapura, with a population of 130 students, and purposive sampling. In addition, data analysis techniques such as data reduction and presentation, and the drawing of conclusions or verification were employed. The results of the study show that the strategy of using the Melajari website leverages classroom media usage patterns, enables active student participation, and fits with the characteristics of arts and cultural learning in the context of visual dance. The influence of using the Melajari website shows that student learning outcomes in the experimental class are approximately 14.28% higher than those in the control class, which does not use the Melajari website. Based on these results, it was concluded that the strategy employed engaged students more actively and enthusiastically and had a positive impact on the learning outcomes of 11 grade students at MA Hidayatullah Martapura. Other researchers wishing to conduct similar research are encouraged to integrate it with other strategies.